회계교육 실태와 개선방안에 관한 연구 -제주지역 특성화고등학교를 중심으로 - 오성렬; Oh, Sung-Ryoel (한국콘텐츠학회 논문지, 16(10), 2016)
In this paper, we did not observe only the actual condition of accounting education, but also proposed the improvements for better education in commercial high schools in Jeju. We expect that those enable the high school students to be interested in accounting. These days, crisis of the accounting education is not only caused by poor educational system, but also is caused in large part by lack of efforts for improving the accounting education. In order to improve the quality of the accounting education and enable the students to be interested in accounting, it is necessary to understand why the students feel difficult about accounting. Learning the reasons enables teachers to educate by much more personalized curriculum, so that those will provide the opportunities to enable the students to pay more attention to accounting. we analyzed the realities in educating accounting by conducting a survey for the students. We also proposed the improvements based on the results of analyzing the realities of the accounting educations. The improvements are followings. First, the accounting education should be educated through various ways. Second, curriculum fitted to the high school students level should be developed. Third, subjects related with accounting should be improved by considering efficiency. 본 연구는 제주지역 특성화고등학교 상업정보계열 기준학과의 회계교육 실태를 분석하여 개선방안을 제시함으로써 제주지역 상업교육을 활성화시켜 좀 더 많은 특성화고등학교 학생들이 회계학에 대한 관심을 제고하고자 한다. 오늘날 회계교육의 위기는 교육제도에서 초래된 측면도 있지만 학교에서 회계교육의 질적 개선을 위한 노력이 부족한데도 상당부분 기인한다. 회계학에 대한 학생들의 관심을 제고하고 회계교육에 대한 질을 향상시키기 위해서는 학생들이 회계교육에서 어떤 내용을 얼마만큼 왜 어려워하는지에 대한 이해가 선행되어야 한다. 이와 같은 이해가 선행될 때 학생들의 눈높이에 맞는 교육이 가능할 것이며 학생들의 회계학에 대한 관심을 제고하는 계기를 제공할 것이다. 본 연구에서는 제주지역 특성화고등학교 학생들에게 설문조사를 실시하여 회계교육 실태를 분석하고 이를 토대로 개선방안을 제시하였다. 개선방안으로는 첫째, 다양한 회계교육 교수방법의 사용 둘째, 고등학교 학생수준에서 이해가능한 회계교과목 교재의 개발 필요 셋째, 효율적인 회계교과목 개선 등이다.